Language, action, and context : the early history of pragmatics in Europe and America, 1780-1930 - Nerlich, Brigitte, 1956- (Amsterdam studies in the theory and history of linguistic science. Studies in the history of the language sciences, 1996)
The roots of pragmatics reach back to Antiquity, especially to rhetoric as one of the three liberal arts. However, until the end of the 18th century proto-pragmatic insights tended to be consigned to the pragmatic, that is rhetoric, wastepaper basket and thus excluded from serious philosophical consideration. It can be said that pragmatics was conceived between 1780 and 1830 in Britain, but also in Germany and in France in post-Lockian and post-Kantian philosophies of language. These early 'conceptions' of pragmatics are described in the first part of the book. The second part of the book looks.